THE MESSAGE OF PEACE IN THE HADITH OF THE COMMAND FOR WARFARE “UMIRTU AN UQĀTIL AL-NĀS”: An Analysis of the Science of Wurūd al-Hadīṡ - Hasbillah, Ahmad 'Ubaydi (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
This article aims to review the understanding of the hadith umirtu an uqātil al-nās, which is often interpreted as an absolute command to engage in warfare. Through a comprehensive study of takhrīj syāmil (comprehensive sourcing) and an analysis of the science of wurūd al-hadīṡ, it can be found that the hadith, which straightforwardly commands fighting non-Muslims, actually contains a call for peace and civility. The study incorporates an examination of the exposition of this hadith in various media, both oral and written, as the primary data source. Through critical discourse analysis, it can be stated that the hadith umirtu an uqātil al-nās does indeed exist and recurs in various cases, but it has been used and understood in different contexts by later generations of Muslims. The population of the chain of narrators (sanad) for this hadith reaches 1,121, which has been traced with the assistance of the Gawami Al-Kalem version 4.5 application. From this population, it was found that 94.6% had a maqbūl status (accepted narration), while the remaining 5.4% were mardūd (rejected narration). In detail, the composition of the maqbūl al-sanad population includes 28.6% (321 sanads) with a sahih status, 41.7% (467 sanads) with a hasan status, and 24.4% (273 chains) with a ḍa’īf status that has been upgraded to hasan li gairih. Furthermore, this article also documents the original contexts of the hadith and its shift in the understanding of Islamic law regarding warfare among the Muslim community. The textual understanding of this hadith is considered potentially prone to radical interpretations if not approached holistically and comprehensively. The research also identifies a phenomenon of neglecting the analysis of wurūd al-hadīṡ and the misuse of sabab wurūd al-hadīṡ and sabab irād al-hadīṡ by hadith scholars. This is supported by the exposition of hadith without considering its context in sahihain and secondary hadith reference books, which leads to an understanding based solely on the general wording of the hadith. [Artikel ini bertujuan untuk meninjau ulang pemahaman tentang hadis umirtu an uqātil al-nās yang sering dipahami sebagai perintah perang secara mutlak. Melalui kajian takhrīj syāmil (komprehensif) dan analisis ilmu wurūd al-hadīṡ, dapat ditemukan bahwa hadis yang secara lugas memerintahkan untuk memerangi orang non-muslim ini ternyata berisi seruan damai dan santun. Kajian tentang eksposisi hadis dalam berbagai media, lisan maupun tulisan menjadi data utama kajian ini. Dengan analisis wacana kritis, dapat dinyatakan bahwa hadis umirtu an uqātil al-nās memang benar adanya dan muncul berulang kali dalam kasus yang berbeda-beda, namun kemudian digunakan dan dipahami dalam konteks yang berbeda oleh generasi muslim belakangan. Populasi sanad hadis ini mencapai 1.121 yang ditelusuri dengan bantuan aplikasi Gawami Al-Kalem versi 4.5. Dari populasi tersebut didapati 94,6% berstatus maqbūl (dapat diterima periwayatannya) dan sisanya yang 5,4% adalah mardūd (tertolak periwayatannya). Secara rinci, komposisi populasi sanad yang maqbūl adalah 28,6% (321 sanad) berstatus sahih; 41,7% (467 sanad) berstatus hasan; dan 24,4 (273 sanad) berstatus ḍa’īf yang naik menjadi hasan li gairih. Selanjutnya, artikel ini juga mendokumentasikan beberapa konteks asli hadis itu dan pergeserannya dalam benak pemahaman umat Islam tentang syariat perang. Pemahaman terhadap lahiriah hadis ini dinilai berpotensi kuat melahirkan paham radikal jika tidak dilakukan secara holistik-komprehensif. Penelitian ini juga menemukan sebuah fenomena pengabaian analisis wurūd al-hadīṡ dan keserampangan penggunaan sabab wurūd al-hadīṡ dan sabab irād al-hadīṡ oleh para pensyarah hadis. Hal ini juga didukung oleh eksposisi hadis yang tanpa konteks wurud ke dalam sahihain serta kitab-kitab hadis sekunder yang menjadi rujukan utama dalam pendidikan Islam, sehingga melahirkan pemahaman yang hanya berpijak pada keumuman lafal hadis.]